Organisational justice: Moderating turnover intention and citizenship behaviour in Eastern Cape nurses - Thobela G. Majali; Nosiphiwo I. Gcaza; Xolile Gcaza (SA Journal of Industrial Psychology)
Orientation: The business sector is engulfed with severe challenges of globalisation in this decade. Hence, companies fight for survival in order to be on the map again. Organisational justice is believed to be key to sustaining various businesses.